Exchange of information: the challenge ahead—Bermuda International Academy of Estate and Trust Law Tokyo May 2019. Issue 1 (27th January 2020) - Robinson, Keith
Abstract: Bermuda has been engaging in tax information exchange with other jurisdictions since the 1980s. This article, which is based upon a paper presented at the annual meeting of the International Academy of Estate and Trusts Law in Tokyo, Japan in May 2019, looks at the historical trend towards information exchange. The article considers in detail the system now in place under Bermuda law for the production of information pursuant to tax information exchange agreements (TIEAs). This requires a court order and the reported case law dealing with challenges to these TIEA orders provides a useful insight into the nature and range of the requests being made by foreign tax authorities.